Kualitas Pendampingan Suami dalam Proses Persalinan - Widi Astuti, Wuri; Mukaromah; Gita Maringga, Estin (STIKES dan AKZI Karya Husada Kediri, 2024)
Childbirth is an important event that is eagerly awaited by every married couple. In addition to being impatient to see her baby born into the world, fear and anxiety about the birth process are also in the mind. So it really needs moral and material support from the husband and family to reduce the mother's anxiety so that the delivery process runs smoothly. The purpose of this research is to know the description of the quality of husband's assistance in the delivery process. The research used descriptive design with a single variable, namely the quality of husband's assistance in the delivery process. The research was carried out in the independent practice of the Mukaromah midwife, Wedoroanom Village, Driyorejo District, Gresik Regency from June 1, 2022 to July 30, 2022. The population of all husbands who accompany mothers in childbirth, using the Total Sampling technique to determine the sample as many as 20 respondents. Data collection using questionnaires and observation sheets. Data analysis used univariate test with editing, coding, and tabulating processes. The results of this study indicate that almost all respondents have good mentoring quality, as many as 17 respondents (85%) and a small proportion of respondents have sufficient quality as many as 3 respondents (15%). The quality of husband's assistance in childbirth is influenced by several factors, including knowledge, age and education. The more mature a husband, the more mature the ability to think as a birth companion so that the delivery process runs smoothly. The need for education to husband about assisting the birth process can accompany the mother in the delivery process so that it runs smoothly.